Oral microbiota–host interaction: the chief culprit of alveolar bone resorption - Xu, Jingyu; Yu, Ling; Ye, Surong; Ye, Zitong; Yang, Luyi; Xu, Xiaoxi (Frontiers in Immunology, 2024)
There exists a bidirectional relationship between oral health and general well-being, with an imbalance in oral symbiotic flora posing a threat to overall human health. Disruptions in the commensal flora can lead to oral diseases, while systemic illnesses can also impact the oral cavity, resulting in the development of oral diseases and disorders. Porphyromonas gingivalis and Fusobacterium nucleatum, known as pathogenic bacteria associated with periodontitis, play a crucial role in linking periodontitis to accompanying systemic diseases. In periodontal tissues, these bacteria, along with their virulence factors, can excessively activate the host immune system through local diffusion, lymphatic circulation, and blood transmission. This immune response disruption contributes to an imbalance in osteoimmune mechanisms, alveolar bone resorption, and potential systemic inflammation. To restore local homeostasis, a deeper understanding of microbiota-host interactions and the immune network phenotype in local tissues is imperative. Defining the immune network phenotype in periodontal tissues offers a promising avenue for investigating the complex characteristics of oral plaque biofilms and exploring the potential relationship between periodontitis and associated systemic diseases. This review aims to provide an overview of the mechanisms underlying Porphyromonas gingivalis-and Fusobacterium nucleatum-induced alveolar bone resorption, as well as the immunophenotypes observed in host periodontal tissues during pathological conditions.